THE IMPACT OF WIRELESS HEADPHONES ON THE CENTRAL NERVOUS SYSTEM - Yuldasheva F. U.; Akhunova Z. Sh.; Ulumbekova A. M.; Karimkhodjayeva S. K.; Mukhamadieva S. B. (The Conference Hub, 2025)
In recent years, wireless headphones have become an integral part of everyday life, significantly simplifying the use of audio devices and providing mobility.